Perceptions of Students on Central System Examinations in Turkey: A Metaphor Analysis Study - Gökhan Baş; Zafer S. Kıvılcım (Anı Publishing, 2019)
The purpose of this research was to investigate students' perceptionsregarding the concept of central system examinations held in Turkey through metaphor analysis. In this research, "phenomenology research design", which is one of the qualitative research designs, was adopted. The participants of the research were consisted of students (n = 372) studying in 2014-2015 education-instruction year in public science, Anatolian, and vocational and technical Anatolian high schools in the province of Nigde, Turkey. The data of the research were collected using the prompt "Central system examinations (LYS, YGS, TEOG, SBS, etc.) are like..., because...". The collected data were analysed through content analysis technique. According to the findings of the research, the students participated in the research were seen to produce a total of 243 well-structured metaphors for the concept of central system examinations. The metaphors produced by the students participated in the research were grouped under six conceptual categories as; "concept as anxiety / torture / disturbing thing", "concept as unfair / unnecessary race", "concept as unconventional, irrelevant, variable, or always existing thing", "concept as turning point of our lives", "concept of selective and determinative of life", and "concept as long or a short-term race".